Liquefaction test and seismic load simulation of saturated sand subgrade with different salt contents - Zhang, Lei; Qiao, Hongxia; Shi, HongZhuang; Ma, Weizhong; Song, Shanglin; Wang, Hanghang (Frontiers in Earth Science, 2023)
On the basis of the highway subgrade construction of North Hobson Salt Lake mining area in Qinghai Province, the soil samples of high saline saturated sand adjacent to the salt lake were remolded, so as to explore the liquefaction effect of saline saturated sand under seismic load. After the indoor geotechnical test, the soil samples were reshaped, and four types of saturated sand containing 0%, 10%, 20% and 30% salt were configured respectively. The liquefaction test of saline saturated sand was carried out by using the GDS dynamic triaxial device to simulate seismic load to investigate the liquefaction mechanism of saturated sand under different salt contents and verify the liquefaction discrimination standard, then based on the data of dynamic elastic modulus, dynamic shear modulus, damping ratio coefficient, and soil density obtained from previous soil tests and dynamic triaxial tests, four subgrade models with different salt contents were constructed using ANSYS simulation software according to actual engineering, and the settlement and deformation of the subgrade were analyzed by inputting EL-concrete seismic waves. The results show that the maximum value of axial stress of saturated sand decreases with the increase of salt content; the load vibration times of saline saturated sand reaching the initial liquefaction state are more than that of common saturated sand; the higher the salt content, the weaker the liquefaction resistance of saturated sand; when the pore pressure ratio coefficient reaches 1, the axial double amplitude strain εd of the soil also reaches 5%, and the soil reaches the initial liquefaction state; the area of shear stress and strain hysteresis curve increases with vibration load, and the elastic modulus decreases gradually; the shear dilation and compaction effects occur in each hysteresis cycle, and the former is greater than the latter.